2016
DOI: 10.1590/1982-021620161833115
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico de uma população com deficiência auditiva

Abstract: Purpose: to characterize the epidemiological profile of the hearing impaired population assisted in a public service regarding sociodemographic, clinical, assistance, communicative and comportamentals aspects. Methods: observational descriptive cross-sectional study conducted with secondary data. The sample consisted of 307 users, from May 2009 to May 2011. Was used protocol for the authorization to deliver Personal Hearing Amplifiers. Results: there was predominance of the users are female, seniors over 60 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
13

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
1
3
0
13
Order By: Relevance
“…Regarding the relative clinical findings, the data corroborate previous studies in terms of the predominance of the sensorineural type [7][8]16 and of the moderate degree [5][6]8,14,16 . The complaints of hearing loss, tinnitus and dizziness coincide with results of a national study that evaluated the audiological profile of adults and the elderly in the city of São Paulo 4 .…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the relative clinical findings, the data corroborate previous studies in terms of the predominance of the sensorineural type [7][8]16 and of the moderate degree [5][6]8,14,16 . The complaints of hearing loss, tinnitus and dizziness coincide with results of a national study that evaluated the audiological profile of adults and the elderly in the city of São Paulo 4 .…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the prevalence of males among FM system users was in agreement with some studies conducted in the country, and in disagreement with others. An epidemiologic research on population with HL, from the same state where this study was developed, indicated prevalence of female users (14) . On the other hand, there is a study form another state, also conducted in public auditory healthcare service, which indicated the prevalence of males (15) .…”
Section: Discussionmentioning
confidence: 93%
“…The auditory healthcare services ensure the audiologic diagnosis, the selection and indication of use of HA and/or CI surgery, besides auditory habilitation or rehabilitation, as well as the supply of the FM system to better include the users who are students. Hence, knowing epidemiologic data of these services is fundamental to the planning process and the adequate decision-making regarding the attention given to the population, the actual needs of the community, and the determining factors for complications and illnesses, or even difficulties in the process of social and educational inclusion (14,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Os grupos com maior risco para esta deficiência são os maiores de 60 anos e as pessoas com menor renda e nível de escolaridade (Béria et al, 2007). Além disto, estudos que traçaram o perfil da população atendida em serviços públicos de reabilitação auditiva indicaram um predomínio de idosos, com baixo nível socioeconômico e de escolaridade (Mondelli & Silva, 2011;Jardim, Maciel & Lemos, 2016).…”
Section: Análise E Planejamentounclassified